Between Culture and Context: What Shapes Māori Perspectives on Capitalism and Government Regulation? - Houkamau, Carla; Lilly, Kieren; Dell, Kiri; Nicholson, Amber; Staniland, Nimbus; Mika, Jason; Sibley, Chris (The International Journal of Indigenous Business, 2026)
This study examines the way Māori (Indigenous to Aotearoa New Zealand) attitudes toward capitalism and government regulation of business vary across the population, challenging homogeneous representations of a single “Māori perspective”. While previous research has explored Indigenous economic models (Anderson et al., 2008) and emphasised the tensions between Indigenous values and market economics, these studies often imply a monolithic Indigenous economic perspective. Using data from Wave 2 of the 2020 Māori Identity and Financial Attitudes Study, we examined 3,241 Māori participants through multiple regression analyses to assess the way cultural identity (iwi importance, cultural efficacy) and employment type (self-employed, paid worker) influence attitudes toward capitalism and government regulation of business. Our findings revealed significant associations between cultural identification, employment position, and economic attitudes. Māori with stronger iwi (tribal) affiliations expressed greater opposition to capitalism and support for business regulation. At the same time, self-employed Māori showed more favourable views toward capitalism and decreased support for government regulation of business. These patterns persisted after controlling for demographic factors. The findings moved beyond homogenising characterisations and towards a more nuanced understanding of the influence of individual circumstances on economic attitudes among Māori.